The Influence of Socio-Economic and Environmental Factors on the Nutritional Status of Toddlers in Urban and Rural Areas in Bangkinang Regency, Riau, Indonesia - Syafriani, Syafriani; Haryati , Haryati; Fitri, Rahmi Pramulia; Afiah, Afiah (Journal of Health and Nutrition Research, 2025)
The nutritional status of toddlers is a critical indicator of sustainable human development. Disparities between urban and rural areas remain a major challenge for equitable child health in Indonesia. This study analyzed socio-economic and environmental factors' influence on toddlers' nutritional status, comparing urban and rural areas. A comparative survey design was used, with 60 respondents - 30 toddlers each from urban and rural areas. Data collection included socio-economic questionnaires, environmental checklists, and WHO Z-score anthropometric measurements. Data were analyzed using regression tests and t-tests. Nutritional status (Z-scores) was significantly better in urban children (1.1 ± 0.3) than rural children (0.5 ± 0.4), (p = 0.000), indicating socioeconomic and environmental disparities between populations. Family income shows the strongest correlation with nutritional status (r = 0.632, p < 0.01) and dominates the multivariate model. Mother's education has a moderate correlation (r = 0.486, p < 0.05), as does environmental score (r = 0.458, p < 0.01), which is dominant in the multivariate context. These findings suggest socioeconomic conditions and environmental quality influence child nutritional outcomes, with income and sanitation being most impactful. The study concludes that toddler nutritional status is determined by interrelated socio-economic and environmental factors varying between urban and rural contexts. These findings underscore the need for region-specific interventions and multi-sectoral policies responsive to local needs.